2015
DOI: 10.1111/psyp.12546
|View full text |Cite
|
Sign up to set email alerts
|

Prediction and perception: Defensive startle modulation

Abstract: Previous research indicates that predictive cues can dampen subsequent defensive reactions. The present study investigated whether effects of cuing are specific to aversive stimuli, using modulation of the blink startle reflex as a measure of emotional reactivity. Participants viewed pictures depicting violence, romance/ erotica, or mundane content. On half of all trials, a cue (color) predicted the content of the upcoming picture; on the remaining trials, scenes were presented without a cue. Acoustic startle … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 31 publications
0
11
0
Order By: Relevance
“…One possible explanation could be the methodological divergences in the experimental designs. Thus, presenting the cues during the several seconds before the picture might have attenuated the emotional response, as reported in previous work focused on anticipation (Sege, Bradley, & Lang, 2015), attenuating therefore the differences between nonregulation and voluntary decrease of negative emotions. Another plausible rationale for the lack of consistency could be the use of varying instructions for decreasing the negative emotions.…”
Section: Methodological Caveats In Prior Psychophysiological Studiesmentioning
confidence: 73%
“…One possible explanation could be the methodological divergences in the experimental designs. Thus, presenting the cues during the several seconds before the picture might have attenuated the emotional response, as reported in previous work focused on anticipation (Sege, Bradley, & Lang, 2015), attenuating therefore the differences between nonregulation and voluntary decrease of negative emotions. Another plausible rationale for the lack of consistency could be the use of varying instructions for decreasing the negative emotions.…”
Section: Methodological Caveats In Prior Psychophysiological Studiesmentioning
confidence: 73%
“…Hamm and colleagues (1997) found that exposure to photos of feared objects potentiated startle blink reflex. Similarly, Sege et al (2015) showed that blink reflexes potentiated when aversive stimuli were viewed without a cue, compared to when mundane scenes were viewed without a cue. Results revealed that reflexes were attenuated when uncued romantic scenes were viewed.…”
Section: Discussion and Future Workmentioning
confidence: 91%
“…Consistent with breathing responses during negative affective states, deeper breathing (e.g., sighing) was found during a mental arithmetic task, while more rapid shallow breathing was evident during an attention task. Eye blinks and respiratory variability have been used as measures not only for differentiating deceptive and truthful behaviors (Marchak, 2013;Seymour et al, 2012), but also for detecting stress levels and deducing emotional responses (Hamm et al, 1997;Sege et al, 2015). During these negative emotional states or under unexpected (Anthony & Graham, 1985), stressful conditions, the frequency of eye blinks may also vary.…”
Section: Discussion and Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, an increase of probe P200 during scary‐ compared to everyday‐predicting cues suggests enhanced attentional registration of peripheral stimuli during aversive anticipation to go along with the enhanced defensive responding. Moving into the exposure window, downregulation of defensive response (startle) priming was then apparent during predictable aversive events for all grades—that is, the priming that arose when viewing unpredictable scary, compared to everyday, pictures disappeared when image content was made predictable (as also seen in adults; Sege et al., 2015). At the same time, probe ERPs were still modulated during predictable scary (relative to everyday) images, and this time reduced positivity in the P300 window was apparent (regardless of grade) as, again, has been observed in adults (see Schupp et al., 1997).…”
Section: Discussionmentioning
confidence: 95%